A STUDY ON THE EFFECTIVENESS OF USING ANIMATION MOVIE COMPARED TO CONVENTIONAL METHOD IN TEACHING NARRATIVE WRITING - Nelson Pandjaitan; Esther Gladys Siringo-ringo; Anne Lou Hendriks (Journal of Language Pedagogy, 2011)
This study is entitled “The Effectiveness of Using Animation Movie Compared toConventional Method in Teaching Narrative Writing.”The purpose of this paper is to know whether or not there is a significant improvement in thestudents’ narrative writing after using the animation movie. The participants involved in thisstudy were 60 pupils in tenth grade senior high school of SMAN 1 Parongpong, Bandung.Section C composed of 28 pupils, while the section D composed of 32 pupils. Section C wastaught using conventional method while section D was taught using animation movie. Thisstudy involved four activities: pilot test, pretest, the implementation of experimental groupand control group, and the posttest. The participants were asked to answer the questions givenin the pretest and posttest.The data obtained were as follows: ô€œ°ô€¬µ= 28, ô€œ°ô€¬¶=32, Î± = 0.05, the mean of pretest ofexperimental group was 53.25 while the mean of pretest for control group was 54.57. Afterthe treatment, the mean of posttest of experimental group was 61.37 and for control groupwas 56.42. From the findings, it was shown that animation movie was effective in improvingstudents’ writing skills as compared to conventional method as indicated by statistical writingscores in posttest of experimental group.